Globalization, physical capital, and human capital nexus with economic growth: evidence from BIMSTEC - Muhammad Raihan Uddin; Nafis Sadik; Md. Mominur Rahman (Research in Globalization)
Policymakers’ main focus is economic growth, particularly in areas like BIMSTEC where structural problems and globalization’s influences greatly affect paths of development. With special focus on the moderating function of globalization, this study examines the link between physical capital, human capital, and economic growth. The paper analyzes the relationships using advanced econometric methods including cross-sectional dependency, stationarity, cointegration, and fully modified ordinary least squares using panel data from 1990 to 2019. The results show a complicated link: while physical and human capital have positive direct effects on growth, globalization negatively moderates these relationships in BIMSTEC due to the region’s diverse economic structures and different degrees of integration with global markets, so transforming them into stronger growth drivers in the long run. Dynamic ordinary least squares and ARDL models’ robustness testing help to validate the results. Especially, although the associations maintain in the long-run, the short run shows no appreciable influence. These findings have significant consequences for policy since they encourage BIMSTEC nation officials to match globalization with capital accumulation policies in order to support sustainable economic development. This paper provides a route for creating long-term development programs that include worldwide possibilities into regional economic strategy.